Molecular-immunohistochemical characteristics of proliferation and apoptosis of tumor cells in colorectal adenocarcinoma - M. A. Shyshkin (Zaporozhye State Medical University, 2018)
Abstract Aim - to study the features of K-RAS transcriptional activity gene, Ki-67 and TP53 mRNA genes expression levels in comparison with the immunohistochemical expression levels of Ki-67, p53 proteins and caspase-3 encoded by them in colorectal adenocarcinoma (CRA) with its progression from the I to the IV stage. Materials and methods. Parallel immunohistochemical and molecular-genetic, pathohistological studies of operational material of CRA from 40 patients (4 study groups - I, II, III, IV stages of the disease according to pTNM classification - 10 cases in each group) with diagnosis of colorectal adenocarcinoma, and also sectional material of 10 fragments of distal colonic wall with normal histological structure were conducted. Results. In comparison with unchanged mucosa of distal colon, CRA is characterized by the increased K-RAS gene and Ki-67 gene activity. As CRA progresses from the I to IV stages, there is an increase in the transcriptional activity of the K-RAS gene and a decrease in the transcriptional activity of the Ki-67 gene in the study groups. The tumor cells are characterized by the medium level of expression of Ki-67, which is the marker of cellular proliferation, herewith the reverse correlation between the Ki-67 expression level and the tumor invasion level is present. CRA is characterized by the increased TP53 gene transcriptional activity with the tendency to elevation, which happens during the progression of the tumor from the I to the IV stage and correlates with the increased K-RAS gene transcriptional activity. CRA is also characterized by the medium p53 expression level and the low level of caspase-3 expression, which is the marker of apoptotic degradation process, which happens in the presence of the reverse correlation between the increased K-RAS gene transcriptional activity and the low level of apoptosis of the tumor cells. Conclusions. The K-RAS and TP53 genes transcriptional activity increases, but the Ki-67 gene transcriptional activity decreases during the process of CRA progression from the I to the IV stage. The inverse correlation between the level of transcription activity of the K-RAS, TP53 genes and apoptosis of tumor cells of the colorectal adenocarcinoma was determined. The decline of proliferation level of the tumor cells, that is observed during the process of CRA progression from the I to the IV stage, is mediated by the signal pathways, which don't have connection with RAS-protein.